Pancreatic diffuse large B-cell lymphoma: a case report and literature review - Shi, Lijun; Wang, Juan; Wei, Li; Ma, Zhongrui; Liu, Xaiohu (Frontiers in Oncology, 2023)
Primary pancreatic lymphoma is an extremely rare malignant tumor that accounts for 1% and 0.5% of all extranodal malignant lymphomas and pancreatic tumors, respectively. The clinical and radiographic characteristics of primary pancreatic lymphoma are non-specific, and it is often misdiagnosed as pancreatic cancer or pancreatic tuberculosis, delaying treatment. The most common histological subtype of primary pancreatic lymphoma is diffuse large B-cell lymphoma. Herein, we report a case of a 48-year-old female patient who was hospitalized for complaints of lower back pain, jaundice, dark brown urine, nausea, and ascites. Radiological evaluation revealed a pancreatic head mass that was diagnosed as diffuse large B-cell lymphoma following ultrasound-guided percutaneous fine-needle biopsy. During hospitalization, the patient’s jaundice worsened, and percutaneous transhepatic drainage was performed. However, hemorrhagic ascites and disorders of consciousness occurred after surgery, and the patient died due to multiple organ failure. Considering the outcome of this case, we reviewed the existing relevant literature on primary pancreatic lymphoma to better understand the disease to facilitate timely diagnosis and initiation of treatment.